Breeding for Striga hemonthica tolerant openpollinated maize varieties in Africa - Kim, S.K. (1994)
A parasitic weed, Striga hermonthica (Del.) Benth., infects millions of hectares of arable land in sub-Saharan Africa, and it threatens production of cereal crops. The objectives of this study were to investigate inheritance in maize (Zea mays L.) inbred lines of tolerance and resistance to S. hermonthica, based on visible host plant symptoms and Striga emergence counts. A diallel cross involving 10 inbreds was tested under Striga infested fields at Mokwa, Nigeria, for 5 yr. Host plant response was rated on a scale of 1 (no symptoms) to 9 (plants dead or dying). Ratings for the crosses ranged from 3.6 (TZi 11 × TZi 12) to 8.3 (TZi 9 × TZi 10). General combining ability (GCA) mean square was roughly twice specific combining ability (SCA) mean square. Data on S. hermonthica emergence counts were taken from the 45 F1 crosses for 2 yr. Average Striga emergence of the 45 crosses ranged from 7.5 (TZi 9 × TZi 12) to 41.0 (TZi 2 × TZi 10). The SCA mean square was roughly 3.5 times greater than the GCA mean square. The results of this study reveal that genetic control for tolerance and resistance of maize genotypes tested to S. hermonthica is polygenic and that the inheritance is quantitative.